Persistent improvement of bone mineral density up to 20 years after treatment of Cushing's syndrome. Issue 2 (1st July 2021) - van Houten, Pepijn; Netea-Maier, Romana; Wagenmakers, Margreet; Roerink, Sean; Hermus, Ad; van de Ven, Annenienke
Abstract : Objective: Cushing's syndrome (CS) is associated with osteoporosis and high fracture risk. Besides male sex, it is unknown which variables influence bone mineral density (BMD) at diagnosis and it is unclear to what extent BMD normalizes during long-term follow-up after treatment of CS. The aim of this study was to determine factors associated with BMD at diagnosis of CS and to determine the long-term course of BMD and fracture rate after successful treatment of CS. Design: Retrospective cross-sectional and longitudinal cohort study. Methods: Data were collected from 231 patients with CS who were treated at the Radboud University Medical Centre between 1968 and 2020. Results: At diagnosis, male sex was associated with lower Z-scores at the lumbar spine (LS) compared with female sex: −0.97s.d. (−1.45 to −0.49) after correction for possible confounders. Shorter duration of symptoms and younger age were also associated with lower Z-scores at diagnosis, while etiology of CS, urinary cortisol excretion and gonadal status were not associated with Z-scores at diagnosis. Z-scores improved up to 20 years after treatment. Fifteen years after treatment, men showed larger improvements of Z-scores than women; +2.56 (1.82–3.30) increase in LS Z-score vs +1.48 (0.96–2.00) respectively. Fracture incidence was highest during the 2 years before diagnosis and decreased after treatment. Conclusion: Male sex, younger age and shorter duration of symptoms are associated with lower BMD at diagnosis of CS. BMD continues to improve up to 20 years after treatment of CS. Fracture rate decreases after treatment of CS.